Juridical Review of The Protection of Intellectual Property Rights in Franchise Agreement - Nafri, Moh.; Maisa; Mantopo, Oscar S (Sinergi International Journal of Law, 2025)
The aim of the research is to find out and analyze the legal protection of intellectual property rights in franchise agreements and to find out and analyze the legal consequences if there is a breach of contract in the franchise agreement. The research method uses normative legal research which uses primary legal materials and secondary legal materials which are then presented in the form of an inductive thinking pattern, namely from specific things to general things. The research results found that as a form of legal protection in franchise agreements, the franchise must be registered with Intellectual Property Rights. Indonesian laws and regulations require a franchise to register its Intellectual Property Rights. The legal consequences if there is a breach of contract in the franchise agreement or one of the parties (Franchisee) does not fulfill its obligations properly and the obligations are not fulfilled because there are elements of negligence and error, then the other party (franchisor) has the right to demand compensation for losses as regulated in Article 1236 and Article 1243 of the Civil Code. The termination of the franchise relationship will also have consequences in terms of the use of IPR, namely Brand Rights and Trade Secrets. The franchisee can no longer use the franchisor's brand and logo. Everything related to it must be returned to the franchisor. The research suggestion is that to provide more certainty and legal protection for IPR owners in the franchise agreement, it is best to always include a clause regulating IPR protection which contains restrictions that the franchisee must comply with. And companies are also advised to make additional agreements with employees to protect IPR.